Research on linearization method of GaN power amplifier based on pre-distorter design - Tang, Jiayi (Nanyang Technological University, 2023)
The need for power amplifier (PA) performance is continually rising with the advent of the 5G communication era and the quick advancement of wireless communication and radio frequency technologies. Many applications, including radar systems, satellite communications, and communications base stations, depend on effective, highly linear power amplifiers. The best material for the next generation of power amplifiers is gallium nitride (GaN), which has good qualities such as a wide band gap, high electron mobility, and high thermal conductivity. Due to the impact of nonlinear distortion, it is currently difficult to create effective and extremely linear GaN power amplifiers. Therefore, in order to enhance the performance of GaN power amplifiers, we suggest a linearization technique based on analog distortion. This study focuses on the simulated pre-distortion technology used in power amplifiers made of gallium nitride (GaN) materials, and it looks for a more effective linearization technique. In order to improve the performance of the RF power amplifier, a novel analog pre distorter design is put forward in this study. It can successfully lower the third-order crossover generator's fundamental frequency and, as a result, lessen interference from the fundamental frequency to the third harmonics. The introduction of the two-channel structure in the circuit design area can significantly increase the performance of the quadrature three-component GaN power amplifier. It has been demonstrated that the RF simulation pre distortion technique may accomplish more efficient linearization through comparative experiments and simulation analyses. It is anticipated that this study will support the further advancement of wireless communication and RF technologies by serving as a helpful resource for the design and optimization of GaN power amplifiers.